Security-aware dual-hop communication for amplify-and-forward relay networks - Fei Ding; Xiaojun Sun; Xiaojin Ding; Ruoyu Su; Dengyin Zhang; Hongbo Zhu (International Journal of Distributed Sensor Networks)
The authentication scheme for vehicular ad hoc networks aims to improve the security and integrity of message delivery. The base station manages a large number of vehicular nodes, so the security communications are non-trivial. In this article, we propose an amplify-and-forward strategy for a dual-hop cooperative network in order to improve secure communications for vehicular ad hoc networks. We assume that each vehicular node equipped with a single antenna and derive closed-form expressions for the secure communication rate calculation. Moreover, we propose a cooperative strategy by jointly considering average power scaling and instantaneous power scaling, which are proved to be able to achieve information security. The simulation result shows that the proposed scheme can achieve better performance in scenarios with different signal-to-noise ratio.